THE EXPEREMENTIONAL STUDIES OF THE GENERATOR OF WIDEBAND SIGNALS WERE CONDUCTED BY THE METHOD OF DIRECT DIGITAL SYNTHESIS - V. V. Murav’iov; S. A. Korenevsky; K. A. Kostykevich; A. A. Stanul (Приборы и методы измерений)
Development and experimental studies of the generator of wideband signals were conducted by the method of direct digital synthesis. Generator allows for the correction of phasefrequency characteristics of the formed broadband signal. The level of spurious radiation was investigated at the output of the frequency mixer in the transfer of the signal spectrum in the band of UHF.